Pertumbuhan Bibit Pinang (Areca catechu L.) Dengan Pemberian Kombinasi Pupuk Kandang Kambing Dan NPK Pada Tanah Ultisol Di Polybag - Hayata, Hayata; Marpaung, Ridawati; Ilham, Febil Nugraha (Universitas Batanghari, 2025)
Cultivating areca nut plants on ultisol soil requires organic and inorganic fertilizers addition to ensure optimal growth. This study aimed to determine the growth of areca nut seedlings using goat manure and NPK fertilizer in polybag of ultisol soil. This research was conducted at Jl. Sebapo, Mestong District, Muaro Jambi Regency, from September to December 2024. The materials used in this experiment were 3-month-old areca nut seedlings from Tri's nursery, ultisol soil, NPK 16:16:16 fertilizer, organic goat manure from Green Exotic Farm Tambak Sari, 4 kg polybags, and water. The tools used are vernier calipers, leaf color charts, hoes, meters/rulers, machetes, scales, stationery, buckets, measuring cups and ovens. The design used in this study was a completely randomized design (CRD) with one factor, namely a combination of goat manure and NPK fertilizer 16:16:16 with 6 levels, namely, k0: Without giving NPK fertilizer and goat manure k1: NPK fertilizer 10 g (100%), k2: Goat manure 30 g (100%), k3: Goat manure 22.5 g (75%) and NPK 2.5 g (25%), k4: Goat manure 15 g (50%) and NPK 5 g (50%), k5: Goat manure 7.5 g (25%) and NPK 7.5 g (75%). This experiment consisted of three replications, each with three sample plants. The application of goat manure and NPK fertilizer to ultisol soil significantly affected plant height, stem diameter, crown dry weight, and leaf color.However, it had no significant effect on the dry weight of the roots and the ratio of the root crown. The application of goat manure and NPK fertilizer in the k4 treatment (15 g goat manure and 5 g NPK/polybag) gave the highest average results in the parameters of plant height (67.54 cm) increased by 21%, stem diameter (16.52 mm) increased by 27% and dry weight of the crown (12.03 g) increased by 44% when compared to no treatment (k0). Keywords: areca nut plants, goat manure, NPK fertilizer, ultisol soil